Pengaruh Komunikasi, Komitmen Organisasidan Insentif Terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Daerah Provinsi Sulawesi Utara - Derek, Vivian Febriani (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
This study aims to determine the influence of communication, organizational commitment and incentives on employee performance of the Public Works and Regional Spatial Planning of North Sulawesi Province.The results of the study show that communication, organizational commitment and incentives simultaneously have a positive and significant effect on employee performance. Communication partially has a significant effect on employee performance. Organizational commitment partially has a significant effect on employee performance. Incentives also partially have a significant effect on employee performanceKeywords: Communication, Organizational Commitment, Incentives and Employee Performance